Effects of micronutrient coated urea on growth and yield of rice - Mohd Dali, Khalida (2015)
Fertilization is important in crop production. To make the plant grow well and healthy, fertilizer must be applied. The increase in rice production can be achieved by efficient and good agricultural practices, water and nutrients inputs. Fertilization provided nutrients for plants grow healthy and give a high yield. When fertilizer is applied to the plants, it will not take up the entire nutrient provided. Nitrogen is very soluble, so it can be easily leached from the soil. The presence of micronutrient deficiency, it is impossible for plant to gain maximum benefit from nitrogen, phosphorus and potassium fertilizer applications. This experiment was conducted to study the effects of micronutrients coated urea on rice and to investigate the performance of micronutrient coated urea on rice yield. The paddy variety MR219 was used in this study. After germination, the seedlings were transferred to glass house at Ladang 2, Universiti Putra Malaysia. In this experiment there were five treatments which is T1 is urea coated with copper, T2 is urea coated with zinc, T3 is urea coated with boron, T4 is urea coated with copper, zinc and boron and lastly T5 is solely urea. There were four replications and each treatment received the same amount of triple super phosphate and muriate of potash. All treatments were treated with different type of coated urea. Recorded data were height of plant, weight of plant and weight of grain. The result showed there were significant differences for all treatment. Hence the most recommended treatment for this study is T4.